A preliminary exploration of the intravoxel incoherent motion applied in the preoperative evaluation of mediastinal lymph node metastasis of lung cancer - Ye, Xin; Chen, Shuo; Tian, Yaru; You, Bin; Zhang, Wenqian; Zhao, Yan; Jiang, Tao; Hu, Bin; Li, Hui (Journal of Thoracic Disease, 2017)
Background: The aim of this study was to investigate the diagnostic value of the intravoxel incoherent motion (IVIM) for distinguishing non-metastatic from metastatic mediastinal lymph nodes in lung cancer. Methods: IVIM-diffusion weighted imaging (DWI) exams were performed preoperatively on 66 patients with lung cancer from October 2015 to June 2016 in Beijing Chao-Yang Hospital, Capital Medical University. Fifty patients underwent enhanced chest computed tomography (CT) in our hospital, while the other 16 patients already had enhanced chest CT images when they were admitted. The patients’ complete preoperative examination included chest magnetic resonance imaging (MRI), enhanced chest CT, head MRI, bone scanning and cardiopulmonary function testing. None of the patients were receiving any treatment for their cancer prior to their evaluation and surgery, including neoadjuvant chemotherapy, radiation therapy, immunotherapy or gene targeted therapy. The following IVIM parameters of the mediastinal lymph nodes were measured: the short axis diameter, apparent diffusion coefficient (ADC), diffusion coefficient (D), pseudo-diffusion coefficient (D*), and perfusion fraction (f). All of the patients underwent lobectomy and lymph node dissection. We compared the CT and MRI results and analysed the IVIM parameters of the pathologically determined non-metastatic and metastatic mediastinal lymph nodes in our 50 patients to generate the ROC curves and determine the best cut-off value for diagnosis. The remaining 16 patients’ IVIM parameters were used to verify the diagnostic cut-off value. This study was approved by the institutional research ethics committee of Beijing Chao-Yang Hospital (2014-S-166), and all the patients signed the MRI informed consent. Results: In this study, MRI was used to measure 140 groups of mediastinal lymph nodes in 50 cases, and the results showed that 19 groups of mediastinal lymph nodes were metastatic, while 121 groups of mediastinal lymph nodes were non-metastatic. The pathological analysis showed that 20 groups of mediastinal lymph nodes were metastatic and 120 groups of mediastinal lymph nodes were non-metastatic. CT was used to measure 273 groups of mediastinal lymph nodes, and the result showed that 34 groups of mediastinal lymph nodes were metastatic, while 239 groups of mediastinal lymph nodes were non-metastatic. The pathological analysis showed that 20 groups of mediastinal lymph nodes were metastatic and 253 groups of mediastinal lymph nodes were non-metastatic. The ADC, D, D*, f values and the short axis diameters of the non-metastatic lymph nodes (n=121) were 2.9370±0.743×10−3, 0.533±0.175×10−3, 0.384±0.121×10−3 mm2/s, 0.426±0.120, 6.903±1.831 mm, respectively, and 1.863±0.691×10−3, 0.454±0.204×10−3, 0.358±0.106×10−3 mm2/s, 0.413±0.085, 7.705±2.213 mm, respectively, for the metastatic lymph nodes (n=19). The ADC and D values of the non-metastatic lymph nodes were significantly higher than the values for the metastatic lymph nodes (P